The Mechanism of the Beneficial Effect of Botulinum Toxin Type a Used in the Treatment of Temporomandibular Joints Dysfunction - Malgorzata, Pihut; Piotr, Ceranowicz; Edward, Kijak (Mini Reviews in Medicinal Chemistry, 2017)
In the course of temporomandibular joint, dysfunctions very often occur to the excessive increase in tension of masticatory muscles, so the main aim of the treatment is reduction of this hypertension of muscles. For this reason, we use botulinum toxin type A, which is produced by Grampositive Clostridium bacteria. There are six serotypes of the toxin: A, B, C, D, E, F, and G. The botulinum toxin type A was first isolated in 1920s. Today, botulinum toxin type A is used increasingly more often as an efficient and patient-friendly therapy in neurology, ophthalmology, neurology, urology and laryngology. The aim of the article was to review the literature and description of the current knowledge concerned with mechanism of action of botulinum toxin type A, clinical applications and metabolic determinants of muscle contraction and the beneficial effect of this drug on the state of muscle tension.
Keywords: neurotransmitter